Nuclear Mean-Field Description of Proton Elastic Scattering by \(^{12,13}\)C at Low Energies - Nguyen, Le Anh; Phan, Huan Nhut; Nguyen, Hoang Phuc (Communications in Physics, 2021)
Nuclear reactions of proton by light nuclei at low energies play a key role in the study of nucleosynthesis which is of interest in nuclear astrophysics. The most fundamental process which is very necessary is the elastic scattering. In this work, we construct a microscopic proton-nucleus potential in order to describe the differential cross-sections over scattering angles of the proton elastic scattering by \(^{12}\)C and \(^{13}\)C in the range of available energies 14 - 22 MeV. The microscopic optical potential is based on the folding model using the effective nucleon-nucleon interaction CDM3Yn. The results show the promising use of the CDM3Yn interactions at low energies, which were originally used for nuclear reactions at intermediate energies. This could be the premise for the study of nuclear reactions using CDM3Yn interaction in astrophysics at low energies